1997
DOI: 10.1128/jvi.71.7.5549-5559.1997
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis analysis of the murine leukemia virus matrix protein: identification of regions important for membrane localization and intracellular transport

Abstract: We have created two sets of substitution mutations in the Moloney murine leukemia virus (Mo-MuLV) matrix protein in order to identify domains involved in association with the plasma membrane and in incorporation of the viral envelope glycoproteins into virus particles. The first set of mutations was targeted at putative membrane-associating regions similar to those of the human immunodeficiency virus type 1 matrix protein, which include a polybasic region at the N terminus of the Mo-MuLV matrix protein and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…The MA protein of type C retroviruses has been suggested to play a critical role in transporting Gag polyproteins to the plasma membrane. Specifically, the basic residues, as well as myristic acid modification within the amino-terminal region of the protein, were found to form a bipartite plasma membranetargeting signal (14,28,38,41,42). In the present study, we found that this signal appears to still be functional even with an amino acid insertion after the basic patch of mutant MuLVs.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The MA protein of type C retroviruses has been suggested to play a critical role in transporting Gag polyproteins to the plasma membrane. Specifically, the basic residues, as well as myristic acid modification within the amino-terminal region of the protein, were found to form a bipartite plasma membranetargeting signal (14,28,38,41,42). In the present study, we found that this signal appears to still be functional even with an amino acid insertion after the basic patch of mutant MuLVs.…”
Section: Discussionsupporting
confidence: 51%
“…The data described above strongly indicate that an insertion of 18 type D-specific amino acids into type C Gag polyproteins altered the viral morphogenesis to preassemble an immature capsid within the cytoplasm. However, these biochemical approaches could not distinguish between intracytoplasmic capsids that had assembled at a cytosolic site, as in type B and D viruses, and intracisternal capsids that had been released into cytoplasmic vacuoles, as in mutant type C viruses (3,10,12,38). Thus, the effects of these amino acids on capsid assembly were more specifically evaluated by EM studies of COS cells transfected with wild-type or mutant proviral DNAs.…”
Section: Synthesis and Processing Of Viral Proteins In Mutant Virusexmentioning
confidence: 99%
See 1 more Smart Citation
“…chimVLPs containing a retroviral gag protein (either MoMLV or simian immunodeficiency virus (SIV) gag) and the antigen of interest (e.g., influenza hemagglutinin and neuraminidase) have been recently described (Guo et al, 2003;Haynes et al, 2009). Unfortunately, the generation of RVF chimVLPs is more complicated because RVFV G and MoMLV gag localize to the Golgi (Gerrard and Nichol, 2002;Schmaljohn and Hooper, 2001;Wasmoen et al, 1988) and plasma membranes (Soneoka et al, 1997), respectively, in mammalian cells. However, over-expression of RVFV G leads to some G N /G C localization at the cell surface (Filone et al, 2006;Gerrard and Nichol, 2002;Gerrard and Nichol, 2007;Liu et al, 2008), which allows the generation of RVF chimVLPs.…”
Section: Generation Of Rvfv Vlps In Insect Cells Has Been Demonstratementioning
confidence: 99%
“…The Gag proteins of retroviruses, and the matrix protein (MA) domains of Gag in particular, have been long recognized as important for the intracellular trafficking of the viral genome (Yuan et al , 1993). Gag proteins are synthesized in the infected cell as a large precursor, and the N‐terminal MA domain of that precursor directs Gag to the plasma membrane (Spearman et al , 1994; Zhou et al , 1994; Ono and Freed, 1999) using a multipartite membrane‐binding signal: a myristic acid moiety covalently attached to the N‐terminal glycine of MA (Rein et al , 1986), a stretch of hydrophobic residues, and basic residues thought to interact with the acidic phospholipids on the inner leaflet of the plasma membrane (Soneoka et al , 1997). The multimerization of Gag during assembly is thought to promote the higher affinity association with the membrane (Ono et al , 2000).…”
Section: Introductionmentioning
confidence: 99%